Immigration, Discrimination, and Trust: A Simply Complex Relationship - Wilkes, Rima; Wu, Cary (Frontiers in Sociology, 2019)
Many immigrants experience discrimination. In this paper we consider how discrimination affects their trust. We make a theoretical case for a formal mediation approach to studying the immigration, discrimination, and trust relationship. This approach shifts attention to the basic fact that the overall levels of discrimination experienced by different immigrant and native-born groups are not the same. We also build on previous empirical research by considering multiple forms of discrimination, multiple types of trust and multiple immigrant/native-born groups. Drawing on the 2013 Canadian General Social Survey data (N = 27,695) we analyze differences in three kinds of trust (generalized trust, trust in specific others, and political trust), and the role of perceived discrimination (ethnic, racial, any), between five immigrant-native groups (Canadian-born whites, Canadian-born people of color, foreign-born whites, foreign-born people of color, and Indigenous people). We find that perceived discrimination is more relevant to general trust and trust in specific others than to political trust. We also find that perceived discrimination explains more of the trust gap between racialized immigrants and the native-born than the gap between non-racialized immigrants and the native-born. The results illustrate that what appears to be a simple relationship is far more complex when attempting to explain group differences.